2023
DOI: 10.1055/a-2009-9809
|View full text |Cite
|
Sign up to set email alerts
|

Ouratea spectabilis and its Biflavanone Ouratein D Exert Potent Anti-inflammatory Activity in MSU Crystal-induced Gout in Mice

Abstract: Gouty arthritis (GA) is an inflammatory arthritis, triggered by the deposition of monosodium urate monohydrate (MSU) crystals causing pain, inflammation, and joint damage. Several drugs are currently employed to manage acute flares of GA, but they either have limited effectiveness or induce severe adverse reactions. Ouratea spectabilis is traditionally used in Brazil to treat gastric ulcers and rheumatism. The ethanolic extract of O. spectabilis stems (OSpC) and four biflavanones (ouratein A-D) isolated thereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…reported that ( 35 ) regular, moderate physical activity prevents acute inflammation in a gout model through the downregulation of circulating neutrophils by TLR2 and the inhibition of serum CXCL1. Ouratea spectabilis, especially ouratein D, acts as an antigout drug by reducing the migration of total inflammatory cells, monocytes and neutrophils and reducing the levels of IL-1β and CXCL1 in synovial tissue ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported that ( 35 ) regular, moderate physical activity prevents acute inflammation in a gout model through the downregulation of circulating neutrophils by TLR2 and the inhibition of serum CXCL1. Ouratea spectabilis, especially ouratein D, acts as an antigout drug by reducing the migration of total inflammatory cells, monocytes and neutrophils and reducing the levels of IL-1β and CXCL1 in synovial tissue ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing research on GA in recent years, well-established anti-GA drugs and decoction have been widely used in the gout population. [178][179][180][181] In addition to this, raising number of pharmaceutical agents are presently undergoing development to counteract GA in accordance with its pathogenesis. NETs have emerged as a pivotal target in the context of GA, and their inhibition has garnered considerable interest as an attractive therapeutic strategy for managing this condition.…”
Section: Nets As Therapeutic Target For Ga Treatmentmentioning
confidence: 99%